2018
DOI: 10.1111/jcmm.13952
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor 21 facilitates peripheral nerve regeneration through suppressing oxidative damage and autophagic cell death

Abstract: Seeking for effective drugs which are beneficial to facilitating axonal regrowth and elongation after peripheral nerve injury (PNI) has gained extensive attention. Fibroblast growth factor 21 (FGF21) is a metabolic factor that regulates blood glucose and lipid homeostasis. However, there is little concern for the potential protective effect of FGF21 on nerve regeneration after PNI and revealing related molecular mechanisms. Here, we firstly found that exogenous FGF21 administration remarkably promoted function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 80 publications
1
41
0
Order By: Relevance
“…Many studies have previously shown that loss of FGF21 causes pathologic damage in multiple animal models, including decreased productivity of pancreatic beta cells and insulin sensitivity (Lee et al, 2018;Wanders et al, 2017), promotion of the development of fatty liver in mice followed by aggravation of liver fibrosis (Singhal et al, 2018), and even aggravation of cisplatin-induced AKI (Holditch et al, 2019). Similarly, overexpression of FGF21 or administration of exogenous FGF21 regulates metabolism, controls the stress response, and attenuates organ damage (So and Leung, 2016;Kang et al, 2018;Lu et al, 2019;Suassuna et al, 2019). Our results are consistent with previous reports.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Many studies have previously shown that loss of FGF21 causes pathologic damage in multiple animal models, including decreased productivity of pancreatic beta cells and insulin sensitivity (Lee et al, 2018;Wanders et al, 2017), promotion of the development of fatty liver in mice followed by aggravation of liver fibrosis (Singhal et al, 2018), and even aggravation of cisplatin-induced AKI (Holditch et al, 2019). Similarly, overexpression of FGF21 or administration of exogenous FGF21 regulates metabolism, controls the stress response, and attenuates organ damage (So and Leung, 2016;Kang et al, 2018;Lu et al, 2019;Suassuna et al, 2019). Our results are consistent with previous reports.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies showed that serum levels of FGF21 are significantly increased in both AKI and CKD, and FGF21 concentration is correlated with the severity of kidney injury (Li F. et al, 2018;Suassuna et al, 2019). However, numerous studies have demonstrated that FGF21 functions in alleviating inflammation and in the regulation of oxidative stress and autophagy-induced apoptosis (Lu et al, 2019;Suassuna et al, 2019). Recent works also showed that FGF21 significantly reduces urinary albumin levels in type II diabetic mice and alleviates kidney injury (So and Leung, 2016;Zhao et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we found that metformin enhanced the number of Nissl bodies and maintained their normal morphology by activating the PI3K/Akt pathway, indicating that metformin treatment can protect neurons from SCI-induced apoptosis through the PI3K/Akt signaling pathway. In addition, Lu et al had verified that fibroblast growth factor 21 improved functional recovery and axonal regeneration through regulating oxidative stress after PNI [59]. Reducing excessive oxidative stress improves the locomotor functional recovery after SCI [60].…”
Section: Discussionmentioning
confidence: 99%
“…Damage to nerve endings promoted by PNI leads to the disuse of the skeletal muscle innervated by the injured branch [ 15 ]. Therefore, ischemic and inflammatory processes are involved, resulting in the emergence of oxidative stress (OS) [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Damage to nerve endings promoted by PNI leads to the disuse of the skeletal muscle innervated by the injured branch [ 15 ]. Therefore, ischemic and inflammatory processes are involved, resulting in the emergence of oxidative stress (OS) [ 15 , 16 ]. Once the peripheral nerve suffers damage, there is accumulation of pro-oxidant substances; simultaneously, the levels of endogenous antioxidants are insufficient to maintain resistance to oxidative damage [ 15 ].…”
Section: Introductionmentioning
confidence: 99%